Influencia de la educación ambiental de niños/as en la calidad de espacios comunes, Escuela “Francisco Zambrano Loor”, Rancho Viejo, Ricaurte – Chone - Andrade Rojas, Byron Mauricio (2019)
This research aimed to evaluate the influence of children's environmental education on the quality of common spaces of the "Francisco Zambrano Loor" school, Rancho Viejo, Ricaurte - Chone. The participatory rural evaluation method was applied through semi-structured surveys and participatory observation. The data was processed in the SPSS 21.0 software to know the differences between the intervention groups and the descriptive variables were analyzed by Student T tests. The study included three phases: the first one allowed weighting the environmental education of children. The second was based on determining the quality of common areas of the school, and the third Implementing an environmental education program based on aquaponic crops and ornamental planting. Weighted the Environmental Education with an average score of 5.75 / 10 points; same as in the final evaluation amounted to 9.88 / 10 points. The quality of the common spaces were presented at Low and Medium levels but amounted to Good and Very Good with the influence of the Environmental Education program. It is concluded that Environmental Education positively influences the quality of the common spaces of the Francisco Zambrano Loor school, with no confidence level of 95%.